La pobreza bidimensional en la ciudad de Loja aplicando los enfoques tradicionales de medición de pobreza por ingresos y necesidades básicas insatisfechas en el año 2014 - Guamán López, Wilson Hernán (2015)
The present work within the problematic is oriented to give answer to the question "how is the reality of poverty in the city of Loja, applying the methods of traditional measurement by income and basic needs unmet, where there is the issue of research raised as: "The dimensional poverty in the city of Loja applying traditional approaches for measuring poverty by income and unmet basic needs in the year 2014 ". it is striking because it is a study involving poverty variable, which has a high degree of influence on human well-being. The General Objective was to define the levels of poverty in the city of Loja through the income and the unmet basic needs and identify their causes, in the year 2014; the study was performed in the city of Loja, where the participants of the research were the homes of the city of Loja. Was used are scientific method shall also include methods of induction, deduction and syntetic- analytical; as techniques, was used the bibliographical and survey and statistics and as instruments the bibliographic data and the questionnaire. As main result, it was found that 24.6 % of the households of Loja city are poor by unmet basic needs (NBI) is say 98 homes; of which 5.3 % are marginal, the 8.1 % and destitute, the 11.2 % moderately poor.